Phase Diagrams of the Aqueous Two-Phase Systems of Poly(ethylene glycol)/Sodium Polyacrylate/Salts - Johansson, Hans-Olof; Feitosa, Eloi [UNESP]; Pessoa Junior, Adalberto (Mdpi Ag, 2011)
Aqueous two-phase systems consisting of polyethylene glycol (PEG), sodium polyacrylate (NaPAA), and a salt have been studied. The effects of the polymer size, salt type (NaCl, Na2SO4, sodium adipate and sodium azelate) and salt concentrations on the position of the binodal curve were investigated. The investigated PEG molecules had a molar mass of 2,000 to 8,000 g/mol, while that of NaPAA was 8,000 g/mol. Experimental phase diagrams, and tie lines and calculated phase diagrams, based on Flory-Huggins theory of polymer solutions are presented. Due to strong enthalpic and entropic balancing forces, the hydrophobicity of the added salt has a strong influence on the position of the binodal, which could be reproduced by model calculations.
Keywords: Polyethylene glycol; sodium polyacrylate; ATPS; Flory-Huggins theory; Phase diagram; hydrophobic ions